Hubungan Self Efficacy dan Dukungan Sosial Teman Sebaya Dengan Self Regulated Learning Pada Mahasiswa Universitas Potensi Utama Medan - Oktariani Oktariani; Abdul Munir; Azhar Aziz (Universitas Medan Area, 2020)
This study aims to examine the relationship between Self Efficacy and peer social support with Self Regulated Learning at Potensi Utama University students. Where the subject of research is a student of Potensi Utama University with a sample of 131 students. Sampling through simple random sampling technique. Data collection is done by using Likert scale which consists of three scale that is Self Efficacy scale, Social Peer Support scale and Self Regulated Learning scale. Data analysis method used is Multiple Regression Analysis. The results obtained that there is a positive relationship between Self Efficacy and social support peers with Self Regulated Learning students of Potensi Utama University. With the value F = 9.511 and the value p = 0.000. Self Efficacy contributes to Self Regulated Learning of 9.3%. Friends' social support contributes to Self Regulated Learning of 7.3%. Self Efficacy and peer social support to Self Regulated Learning as much as 12.9% this means there are still 87.1% other factors that can affect Self Regulated Learning. From these results it is expected for the Potensi Utama University Medan to improve students' ability in managing Self Efficacy in a better direction, build a conducive atmosphere that leads to peer social support, and create learning conditions that lead students to learn independently.